Security in Distributed, Grid, Mobile, and Pervasive Computing - Xiao, Yang (Taylor & Francis, 2007)
Despite recent dramatic advances in computer security regarding the proliferation of services and applications, security threats are still major impediments in the deployment of these services. Paying serious attention to these issues, Security in Distributed, Grid, Mobile, and Pervasive Computing focuses on the increasing demand to guarantee privacy, integrity, and availability of resources in networks and distributed systems. A rich and useful presentation of strategies for security issues, the book covers each computing area in separate sections. It first reviews security issues and challenges in content distribution networks, describes key agreement protocols based on the Diffie-Hellman key exchange and key management protocols for complex distributed systems like the Internet, and discusses securing design patterns for distributed systems. The next section focuses on security in mobile computing and wireless networks, covering wireless authentication methods, secure data aggregation, and anonymous routing protocol. After a section on grid computing security, the book presents an overview of security solutions for pervasive healthcare systems and surveys wireless sensor network security. With more and more vital information stored on computers, security professionals need to know how to combat threats and complications. Offering strategies to tackle these issues, this book provides essential security information for researchers, practitioners, educators, and graduate students in the field.